Impact of Time Constants of Reactive Power Sources on Short-Term Voltage Stability - Scheiner, Elisabeth; Burlakin, Ilya; Strunz, Niklas; Raab, Alexander; Mehlmann, Gert; Luther, Matthias (2022 IEEE Transportation Electrification Conference and Expo (ITEC), 2022)
As a result of the enduring change in power systems the risk of blackouts caused by voltage instability is growing. This paper addresses the challenges of future requirements and Var equipment. The focus is on enhancing the short-term dynamic performance of future electrical power systems. In contrast to traditional steady-state considerations, possible placement options of reactive power sources using dynamic stability indicators based on voltage trajectories are determined. After identifying worst-case fault scenarios based on the Contingency Severity Index (CSI), different time constants for the reactive power control of MSC and STATCOM and their effects on the short-term voltage stability are investigated. The preselection is used to reduce the computational effort and is based on indicators that are determined using RMS calculations. The approach is tested using a modified Nordic Test System with a 35% share of renewable energy source
Keywords: dynamic reactive power compensation; dynamic security; MSC; short-term voltage stability; STATCOM